Tuning microstructure and mechanical and wear resistance of ZrNbTiMo refractory high-entropy alloy films via sputtering power - Liu, Xinyu; Cai, Wumin; Zhang, Yan; Wang, Linqing; Wang, Junjun (Frontiers in Materials, 2023)
High-entropy alloy (HEA) films exhibit many excellent performances and have attracted wide attention. Here, we synthesized a series of ZrNbTiMo refractory high-entropy alloy (RHEA) films by magnetron sputtering with sputtering power from 90 W to 210 W. The effects of sputtering power on the microstructure, mechanics, and tribological properties of this novel ZrNbTiMo RHEA films were investigated. The ZrNbTiMo RHEA films possess a nanocomposite structure composed of a nanocrystal phase and an amorphous phase. With the sputtering power increasing, the crystallinity of the film firstly increases from 13.03 % to 20.07 % and then decreases to 2.40 %. The ZrNbTiMo films deposited at 150 W exhibit a high hardness of 7.5 GPa, a toughness of 0.437 MPa × m1/2, and better wear resistance (wear rate: 5.223 × 10−7 mm3/N∙m) than other films. The growth mechanism of nanocrystalline was explained by the competitive relationship between diffusion ability and available time of deposited atom. The toughening and wear resistance mechanisms of the ZrNbTiMo film were investigated in detail.